2006
DOI: 10.1038/sj.emboj.7601054
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the anaphase promoting complex by HTLV-1 tax leads to senescence

Abstract: The human T-lymphotropic virus type 1 (HTLV-1) Tax binds the anaphase promoting complex (APC) and activates it ahead of schedule. Here, we show that APC activation by Tax induces rapid senescence (tax-IRS) independently of p53 and pRB. In response to tax, cyclin A, cyclin B1, securin, and Skp2 becomes polyubiquitinated and degraded starting in S phase. This is followed by a surge in p21 CIP1/WAF1 and p27 KIP1 in mid to late S and G 2 /M leading to a permanent G 1 arrest. Tax-positive HTLV-1-transformed T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(177 citation statements)
references
References 36 publications
12
164
1
Order By: Relevance
“…The fate of these cells would therefore be dependent on the pleiotropic activities of this viral protein, which dysregulates the transcription of genes involved in cellular proliferation, cell cycle control, apoptosis, and rapid senescence, mainly through the constitutive activation of the NF-B pathway (14,24,41). Thus, these Taxexpressing cells might either undergo programmed cell death or survive and/or proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of these cells would therefore be dependent on the pleiotropic activities of this viral protein, which dysregulates the transcription of genes involved in cellular proliferation, cell cycle control, apoptosis, and rapid senescence, mainly through the constitutive activation of the NF-B pathway (14,24,41). Thus, these Taxexpressing cells might either undergo programmed cell death or survive and/or proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indeed demonstrated that Tax-expressing cells undergo ATM/ATRdependent cell cycle delay in S-G 2 phases, G 1 arrest, and senescence because of a surge of p21 Waf1/Cip1 expression, or even apoptosis. [36][37][38][39][40] Although these observations appear contradictory with the ability of Tax to speed up S phase progression, several lines of evidence suggest that pro-mitotic and antiproliferative activities have to be considered as interconnected processes. Indeed, the ATM/ATR-dependent phosphorylation of H2AX in Tax-expressing cells suggests that unscheduled activation of replication origins creates replicative lesions that alarm the DDR machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the pleiotropic effects of Tax on host cells include potent nuclear factor kappa B (NF-!B) activation (26,82,178,187,192,194) and cell cycle perturbation (90,96,108,111,112,118,145). Tax has been shown to activate the expression of interleukin-2 (IL-2), IL-2R", IL-3, IL-4, granulocyte-macrophage colony stimulating factor, proliferating cell nuclear antigen (PCNA), transforming growth factor beta (TGF-#), mimentin, proenkephalin, egr-1 (Krox20), egr-2 (Krox24), fra-1, c-fos, c-myc, c-sis, bcl-xL, c-Jun, JunB and JunD (105).…”
Section: Overview Of Htlv Taxmentioning
confidence: 99%
“…In essence, Tax activates the cellular program for mitotic exit far in advance of its normal schedule. Tax-induced APC is often accompanied by severe mitotic abnormalities associated with the premature loss of cyclin A, cyclin B1, securin, and Skp2, the substrate targeting subunit of SCF Skp2 , another E3 ubiquitin ligase (96,97). Importantly, the loss of Skp2 renders SCF inactive and dramatically stabilizes its substrate, p27 KIP1 , the major G1/S cyclin-dependent kinases inhibitors (CKI).…”
Section: Tax Effects On Apcmentioning
confidence: 99%
See 1 more Smart Citation